Information Communications and Technology (ICT) Abuse in the Malaysian Public Sector: The Influence of Ethical, Organisational Bond and General Deterrence Factors (Nota Penyelidikan). - Sapiah Sakri; Juhana Salim; Tengku Mohammed Tengku Sembok (Universiti Kebangsaan Malaysia, 2012)
Despite continuous effort to reduce ICT abuse, ICT security problems still persist such that ICT security experts and practitioners are kept struggling to find ways to combat the problems which are closely related to deviant human behaviour. Previous studies have investigated the causal relationships between security efforts and ICT abuse but studies on ICT abuse in the Malaysian public sector are still rare. This research aims at identifying significant factors that influence ICT abuse as an input to develop and validate an ICT abuse model within the Malaysian public sector setting. The proposed model contributes to the theoretical body of knowledge on ICT abuse by adopting multidisciplinary solutions whereby ethical factors from the discipline of psychology, organisational bond factors from the discipline of socio-criminology and general deterrence factors from the discipline of ICT security are examined and synthesised.